P304 Exploring attitudes to virtual gastroenterology clinic provision in the South West: a regional staff survey. (19th June 2022) - Abeysekera, Kushala; Saunsbury, Emma; Sheiybani, Giovanna; Belfield, Katherine; Bradbury, Molly; Creamer, John; Katwal, Prakash; Lin, Simeng; Mole, Sean; Pillai, Leksmy; Pohl, Keith; Wesley, Emma
Abstract : Introduction: The COVID-19 pandemic has forced healthcare professionals (HCPs) to rapidly alter their delivery of outpatient services. Perceived benefits include reducing unnecessary travel and waiting times. However, as one of the geographically largest training regions in the UK, we aimed to determine satisfaction levels amongst gastroenterology HCPs with the "new normal". Methods: Satisfaction surveys were disseminated electronically across 13 acute trusts in the South West between June and August 2021. These consisted of multiple choice questions and Likert 5-scale ranking questions, ranging from 'strongly agree' to 'strongly disagree'. Virtual clinics were defined as telephone or video consultations. Results: 64 HCPs from 7 trusts responded (52% consultants; 23% registrars; 19% nurse specialists; 6% dieticians). 80% had performed phone consultations and 23% were providing video consultations. 94% of participants stated face-to-face (F2F) consultations remained their preferred mode of clinic, whilst video consultation was the least favoured for new patients. For follow-up patients, the most favoured combination was phone and F2F consultations, followed by solely F2F consultations. Less than a third of respondents strongly agreed that they would be comfortable using a computer for video consultation (32%), compared to over half when using phone instead (53%). 47% of HCPs stated virtual clinics were now the default clinic mode in their trust. The majority of respondents found it difficult to develop a rapport with remote consultations, with only 19% respondents stating this was not an issue. There was equipoise about whether time efficiency improved with virtual consultations, though 60% of respondents agreed or strongly agreed that virtually delivered clinics can reduce clinic non-attendance. Two thirds of respondents did not have a local process to identify patients who would not benefit from virtual clinics, whilst over three quarters did not have technical support to troubleshoot issues during virtual clinics (78%). Only five respondents (8%) thought it was straightforward to include an interpreter on a virtual consultation and 70.3% had difficulties including relatives on virtual calls. Conclusions: Gastroenterology departments in the South West continue to adapt to delivery of virtual clinics, through a predominantly telephone format. There is consensus that follow-up patients do not routinely need to F2F appointments, but new patients should primarily be seen F2F. Departments should have clear protocols to identify patients that will not benefit from virtual consultations. Finally, robust strategies are required to accommodate patients whose first language is not English to ensure they are not disproportionately disadvantaged.